(untitled) (Journal of Economic Research & Business Administration, 2025)
This study examines the current state of local self-governance (LSG) in Kazakhstan and the mechanisms for improving its effectiveness. Local self-government bodies play a vital role in regional development and enhancing citizens’ quality of life, yet their potential is hindered by significant challenges, including financial dependence on central authorities, limited citizen participation, and insufficient transparency. The purpose of the research is to analyze the potential implementation of the Local Governance Performance Index (LGPI) in Kazakhstan as an effective tool for assessing and improving the performance of local self-governance. The study focuses on exploring LGPI’s international applications and its relevance in addressing governance inefficiencies in Kazakhstan. The research highlights the potential of LGPI to address key challenges in LSG by introducing measurable performance indicators. Its implementation could significantly enhance transparency, public participation, and service delivery at the local level, contributing to the modernization of governance in Kazakhstan. The study employs a qualitative methodology, including an analysis of the regulatory framework, expert interviews with local governance specialists, and a comparative review of international practices. This approach identifies actionable steps for integrating LGPI into Kazakhstan’s governance system. The research reveals that adopting LGPI could improve accountability and foster sustainable regional development by addressing governance gaps. The findings demonstrate the need for feedback mechanisms and measurable metrics to promote inclusive decision-making processes. This work contributes to the ongoing decentralization reforms in Kazakhstan by providing a practical roadmap for enhancing financial and administrative autonomy. It offers evidence-based recommendations for policymakers to strengthen the effectiveness and transparency of LSG bodies. The implementation of LGPI in Kazakhstan can serve as a foundation for systematic governance improvement. It would aid in creating a more transparent, inclusive, and participatory local governance system while aligning with international best practices. Key words: local governance, decentralization, LGPI, public services.